Pelatihan Pembuatan Mie dari Limbah Kulit Buah Naga (Hylocereus Polyrhizus) di Desa Gona Kecamatan Kajuara - Perdana, Rini; Muhammad Ikhsan Sukaria (Education and Talent Development Center Indonesia, 2024)
The noodle-making training from dragon fruit peel waste (Hylocereus polyrhizus) in Gona Village, Kajuara Subdistrict, is a community service initiative aimed at developing local potential. About 20 members of the Gona Village community in Kajuara Subdistrict attended the socialization activity. The community participated in a socialization session regarding the nutritional content and product development based on dragon fruit peel. Organoleptic testing results of the product indicated that dragon fruit peel noodles were generally considered good by most people. Based on the results of this community service, it can be concluded that dragon fruit peel waste can be processed into noodles that have nutritional and economic value, which can be utilized to improve nutrition and income for the community in Gona Village.